Efficient heterogeneous photodegradation of Eosin Y by oxidized pyrite using the photo-Fenton process. (January 2023) - Zhang, Wanjia; Jiang, Xu; Ralston, John; Cao, Jian; Jin, Xin; Sun, Wei; Gao, Zhiyong
Graphical abstract: Highlights: Pyrite has Fe(II) and Fe(III) components and displays excellent photoelectric properties. Based on photo-Fenton reaction, a cheap, green and efficient method to degrade Eosin Y using pyrite was developed. The degradation ability of pyrite for Eosin Y is directly proportional to oxidation degree. Efficient photodegradation (> 90%) of Eosin Y occurs by H2 O2, O2 – and OH under optimum conditions. Abstract: Eosin Y as a common dye is often used for cotton, silk and other materials. However, Eosin Y is highly toxic and difficult to degrade. Typically, 20% is lost during the printing and dyeing process to produce organic dye wastewater, which can cause serious harm to the environment and human health. Current treatment methods do not satisfy the dual requirements of environmental protection and cost. Pyrite (FeS2 ) is the most common sulfide gangue mineral and displays excellent photoelectric properties. We chose pyrite as a promising photocatalyst to degrade organic dye wastewater because of its Fe(Ⅱ) and Fe(III) components, which participate in the photo-Fenton reaction. In this study, we use a photocatalytic reaction device incorporating naturally oxidized pyrite as a photocatalytic material to degrade Eosin Y. More than 90% degradation was achieved, when either white or green light was used as the light source over 3 h, in the pH range was 6–8, with an initial concentration of Eosin Y of 10 mg/L. Surprisingly, even if the addition of the pyrite sample is very low, it can still be recycled. The reaction mechanism was explored by composition analysis, scanning electron microscopy-energy dispersive spectroscopy, X-ray photoelectron spectroscopy, electron paramagnetic resonance and radical trapping experiments. This study suggests a novel method use for the high-value utilization of sulfide tailings.